Teletrabalho transnacional : a garantia dos direitos humanos dos trabalhadores no plano internacional perante o princípio da norma mais favorável - Bitencourt, Manoela de (2014)
Globalization, modern computing, and information and communication technologies enabled the realization of work by distance and in another country, called transnational telework. Thus, it arises an international agreement which may have more than one applicable law originated from different sovereignties. In this context, the occurrence of a conflict of labor laws in space is possible, reason why this study perquire on the law applicable to this contract, in order to regulate the legal situation. Private international law indicates connection elements for the solution of the litigation, whereas labor law also elect its connecting criterion. Among others, it is emphasized the principle of territoriality as set out in Bustamante Code, and the most favorable standard principle. The research uses the hypothetical-deductive method of approach and the bibliographic search procedure method. The aim is to delimit the solvers criteria of litigation and show whether it is effective the guardianship of labor human rights to apply existing connection elements; and also checks whether the principle of territoriality would not be exceeded in when it comes to teleworking, inasmuch as the place of supply of services is virtual. Conferring value to the principle the most favorable standard, in order to protect effectively the human rights of workers, it is understood that the connecting element that should prevail and regulate the legal relationship of transnational telework is the law of the country that, as a whole, bring major benefits to the teleworkers. Moreover, the principle of territoriality would not be overcome, since it is possible to make a reinterpretation of the place of supply of services, which may be the country where it has corporate headquarters, which would effect the principle of equality because it would be applying the same law to employees of the same company. Subsisting that connecting factor - which is taken into consideration along with others who have close connection with the legal relationship - is possible to analyze if the law of the country where labor is running (reinterpreted) is the most favorable among those that may relate to the contract. The the most favorable standard principle is provided in caput of Federal Constitution Article. 7, which provides for the improvement of the worker's status Thusthe legislator, the employer and the State, in general, should ensure a minimum protection to workers as a way of effectuation of their human rights, even in order to promote substantive equality among employer and employee. Finally, as the labor law is composed almost entirely of rules of public policy, and because the employment relationship is asymmetric, the employee deserves to be protected, and the State should not leave its subject, when in unknown horizons, be subjected to less favorable conditions than those existing in his country of origin. In this context, it is understood, with this research, that among the standards that focus on this relationship, should be applied the most favorable to the employee, being possible, so, ensure prevention of social regression.